Analysis of the effects of storage conditions on the preservation of soybean quality and the prevention of the self-heating process and the occurrence of fires - Milanko Verica J.; Gavanski Dušan G.; Laban Mirjana Đ. (Hemijska Industrija, 2012)
After harvest, oilseed raw materials must be stored for a longer or shorter period of time before further processing. The task of storage is the safekeeping of the stored material with a minimal loss in quality. In order to preserve wet grain until processing, it is necessary to provide proper storage conditions. For this purpose, storage in the atmosphere of inert gases as well as storage in hermetically closed storages is applied. Such method is uncommon for oil cultures in domestic practice. Experimental research, analyzed in this paper, with emphasis on the effects of storage conditions on the preservation of soybean grain quality and the prevention of possibilities of the occurrence of the self-heating and self-ignition process, confirms the advantages of application of such method of storage for soybean grain. Soybean with the moisture content of 10.99% and 16.96% is stored in steel semi-industrial silo cells with carbon-dioxide atmosphere, and in hermetically sealed cell. The changes in temperature in the silo cells, changes in moisture content and discoloration of the soybean grains, as well as the amount of oil and protein in the grain were monitored during the experiment. The quality of the oil in grain was determined through the content of free fatty acids. The results of the research showed that, during longer period of time (216 days), the quality of the soybean grain in the sample with higher moisture content (16,96%) was preserved when storage was performed in carbon dioxide atmosphere. The storage of wet grain in a hermetically closed cell, in relation to the grain kept in carbon dioxide atmosphere, did not record significant differences in the examined indicators. Since the storage under controlled conditions did not result in the development of processes that would lead to the spontaneous heating of the soybean mass, the recommendation is to introduce such storage method for oilseed raw materials into domestic practice, with the additional aim of increasing the degree of protection against fire and explosions.